Firefly genomes illuminate parallel origins of bioluminescence in beetles - Fallon, Timothy R (eLife Sciences Publications, 2018)
Fireflies and their luminous courtships have inspired centuries of scientific study. Today firefly luciferase is widely used in biotechnology, but the evolutionary origin of bioluminescence within beetles remains unclear. To shed light on this long-standing question, we sequenced the genomes of two firefly species that diverged over 100 million-years-ago: the North American Photinus pyralis and Japanese Aquatica lateralis. To compare bioluminescent origins, we also sequenced the genome of a related click beetle, the Caribbean Ignelater luminosus, with bioluminescent biochemistry near-identical to fireflies, but anatomically unique light organs, suggesting the intriguing hypothesis of parallel gains of bioluminescence. Our analyses support independent gains of bioluminescence in fireflies and click beetles, and provide new insights into the genes, chemical defenses, and symbionts that evolved alongside their luminous lifestyle.